Young male motorcycle rider perception response times to abrupt- and gradual-onset hazards. (February 2022) - Wong, Grace; Wong, Yiik Diew
Highlights: Direction deviation is a more appropriate onset for gradual-onset hazards. Response times to gradual-onset hazards were longer than to abrupt-onset hazards. Unlicensed subjects tended to underperform relative to licensed riders in hazard scenarios. Average response times to four turn-across-path scenarios were between 0.77 s and 1.15 s. Abstract: Response time (RT) measures in crash reconstruction are inherently constrained by the need to define a start point (onset). In straight-forward situations where the hazard appears abruptly from behind an obstruction (abrupt onset), hazard onset is typically defined as when the hazard is first visible to the motorist. In contrast, in scenarios where there is no clearly defined point of entry (gradual onset), and the potential hazard gradually transitions to an immediate hazard, the onset point is more ambiguous. In this study, a reasonable hazard onset was proposed for measuring RTs of motorcycle riders to gradual-onset hazards, following which the RTs to abrupt- and gradual-onset hazards were determined and compared. A study on motorcycle rider RTs was conducted in Singapore in which a sample of young male adults (licensed riders with more than one year's effective riding experience, and unlicensed subjects) were equipped with eye tracking glasses and were presented with two pairs of abrupt-/ gradual-onset hazard scenarios on a simple motorcycle simulator. Their RTs were recorded. Initial deviation from the straight path (start of turning manoeuvre) of the intruding hazard vehicle was determined to be a more appropriate onset (start point when measuring RTs) for gradual-onset hazards when compared with referencing the onset against travel lane incursions. Participants generally took longer to respond to gradual-onset hazards than abrupt-onset hazards. Unlicensed subjects tended to underperform relative to licensed riders. The findings from this study contribute to the literature in the relatively novel field of motorcycle RTs and should be of interest to crash reconstructionists as well road safety professionals in designing road operations.